Pharmaceutical care and evaluation of adherence to antiretroviral therapy in people living with HIV/AIDS - Marcio Rodrigo Schoenherr; Lucimary Afonso dos Santos; Eduardo Remor; Angela Maria Campanha (Universidade de São Paulo, 2022)
Abstract Highly Active Antiretroviral therapy (HAART) depends on optimal adherence to be effective. Pharmacotherapeutic follow-up can be used as a strategy for treatment fidelity. To provide pharmaceutical care for HAART patients, to assess adherence, to identify and resolve drug related problems (DRP). This is a prospective, interventional study aimed at people on HAART. Data was collected using the pharmacotherapeutic follow-up form and CEAT-VIH. There was a predominance of women (59%), older than 33 years (75%), mostly single (43%). Regarding adherence, 64% had insufficient adherence at the start of the study, while 36% had strict/adequate adherence. After the pharmacotherapeutic follow-up, 70% presented strict/adequate adherence. Regarding HAART, the relationship between adhesion versus time of HAART and adherence versus regimen used was significant, considering that less time of therapy and regimen containing protease inhibitors are predictors for insufficient adherence. Regarding the DRP identified (f=77), missed pills (32%), untreated disease, incorrect management frequency, and undue self-medication (12%) were the most frequent. Pharmaceutical interventions (f=137) were predominantly advising related to specific pharmacological treatment (32%), non-pharmacological measures (20%), and medication suspension (9%). Pharmaceutical care was shown to be animportant strategy, within the multi professional team, to improve adherence, besides identifying and resolving DRP.